2004
DOI: 10.1126/science.1091230
|View full text |Cite
|
Sign up to set email alerts
|

ABAD Directly Links Aß to Mitochondrial Toxicity in Alzheimer's Disease

Abstract: Mitochondrial dysfunction is a hallmark of beta-amyloid (Abeta)-induced neuronal toxicity in Alzheimer's disease (AD). Here, we demonstrate that Abeta-binding alcohol dehydrogenase (ABAD) is a direct molecular link from Abeta to mitochondrial toxicity. Abeta interacts with ABAD in the mitochondria of AD patients and transgenic mice. The crystal structure of Abeta-bound ABAD shows substantial deformation of the active site that prevents nicotinamide adenine dinucleotide (NAD) binding. An ABAD peptide specifical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

43
1,129
0
9

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 1,188 publications
(1,210 citation statements)
references
References 21 publications
43
1,129
0
9
Order By: Relevance
“…Supporting Information Available: Synthetic procedures for compounds 1-10, enzymology assay, cell imaging protocols, and complete ref 8. This material is available free of charge via the Internet at http://pubs.acs.org.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting Information Available: Synthetic procedures for compounds 1-10, enzymology assay, cell imaging protocols, and complete ref 8. This material is available free of charge via the Internet at http://pubs.acs.org.…”
Section: Discussionmentioning
confidence: 99%
“…The Aβ peptide can also potentially cause mPTP opening in vivo as it induces mitochondrial swelling, decreases mitochondrial membrane potential, and potentiates the effect of mPTP inducers in isolated brain mitochondria (Du et al., 2008; Moreira, Santos, Moreno, & Oliveira, 2001; Shevtzova, Kireeva, & Bachurin, 2001). This can be due to an indirect effect on the pore as the Aβ peptide has the ability to enhance intracellular calcium (Abramov, Canevari, & Duchen, 2004; Chin, Tse, Harris, & Jhamandas, 2006) and to induce oxidative stress (Lustbader et al., 2004; Reddy & Beal, 2008), which is increasingly recognized as a key factor in neurodegenerative disorders. These effects are possible mechanisms contributing to mPTP opening.…”
Section: Evidence For the Involvement Of Mptp Opening In Age‐associatmentioning
confidence: 99%
“…Lustbader et al, demonstrated that Aβ binds to the mitochondrial β-amyloid-binding alcohol dehydrogenase (ABAD) (Lustbader et al, 2004), an up-regulated enzyme in patients' brain, which resulted in free radical production and oxidative stress, and increased expression of the cytosolic antioxidant enzyme peroxiredoxin II as a cellular defense response (Yao et al, 2007;Ahsan et al, 2009). In fact, the inhibition of the Aβ-ABAD interaction has been shown to reduce Aβ accumulation and to improve mitochondrial function in transgenic mice and neuroblastoma cells (Lim et al, 2011;Yao et al, 2011).…”
Section: In Alzheimer´s Diseasementioning
confidence: 99%